2019
DOI: 10.1111/tbed.13147
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of clade 2.3.4.4 H5N8 and H5N2 highly pathogenic avian influenza viruses in peridomestic wild birds in the U.S.

Abstract: Summary European starlings (Sturnus vulgaris), house sparrows (Passer domesticus) and rock pigeons (Columba livia) are all wild birds commonly found in large numbers in and around human dwellings and domestic livestock operations. This study evaluated the susceptibility of these species to three strains of highly pathogenic avian influenza virus (HP AIV) clade 2.3.4.4 isolated in the U.S.. Experimental infection of European starlings and rock pigeons did not result in any overt signs attributable to AIV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…In general, our results are in line with previous studies that have experimentally assessed IAV infection dynamics in starlings [18,29,[35][36][37][38][39] through experimental inoculations. In general, these studies show that starlings can become infected with IAVs and seroconvert but see [36], primarily shed via the oral cavity but see [29], and exhibit limited, if any, contact transmission [35,38]. While a variety of IAV subtypes have been tested (H2, H3, H4, H5, and H7,…”
Section: Plos Pathogenssupporting
confidence: 92%
“…In general, our results are in line with previous studies that have experimentally assessed IAV infection dynamics in starlings [18,29,[35][36][37][38][39] through experimental inoculations. In general, these studies show that starlings can become infected with IAVs and seroconvert but see [36], primarily shed via the oral cavity but see [29], and exhibit limited, if any, contact transmission [35,38]. While a variety of IAV subtypes have been tested (H2, H3, H4, H5, and H7,…”
Section: Plos Pathogenssupporting
confidence: 92%
“…Reading recently published reports is another way to obtain valuable information towards the development of science‐based management strategies. Example topics that are relevant towards the consideration and development of mitigation strategies for HPAI in North American wildlife include the susceptibility of common wild and peridomestic bird species to infection and clinical disease when exposed to clade 2.3.4.4 Gs/GD HPAI viruses (Pantin‐Jackwood et al 2016, Spackman et al 2017, Kwon et al 2018, Bosco‐Lauth et al 2019, Shearn‐Bochsler et al 2019, Luczo et al 2020) and the persistence of infectious AI viruses in surface waters of North American wetlands (Keeler et al 2014, Ramey et al 2021). Other topics relevant to specific management areas include the current distribution, abundance, movement patterns, and interaction of susceptible wildlife species with domestic species in or near management areas, and understanding past outbreaks or susceptibility of infection in wildlife species that occur within a management area.…”
Section: Preparing For Future Outbreaks Of Hpai In Wild Birdsmentioning
confidence: 99%
“…Similar to most studies of IAV in pigeons, a test of another recently-emerged virus, HP H5N8 clade 2.3.4.4, showed that most experimentally inoculated pigeons became infected, but with limited viral shedding across a brief period and no transmission to contact pigeons [ 65 ]. In another study using the HP H5N8 clade 2.3.4.4 virus, no inoculated pigeons showed clinical signs or shed virus [ 66 ]. Another experimental inoculation with an HP clade 2.3.4.4 virus, but in this case an H5N6 virus, showed that several pigeons became infected and shed virus at moderately high levels; nonetheless, no contact chickens became infected [ 67 ].…”
Section: Pigeons Doves: Order Columbiformes Family Columbidaementioning
confidence: 99%